2011
DOI: 10.1146/annurev.nutr.012809.104807
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D in Pregnancy and Lactation in Humans

Abstract: Concerns exist about the adequacy of vitamin D in pregnant and lactating women. This review assesses the evidence that maternal vitamin D status influences maternal, fetal, and breast-fed infant bone health; maternal adverse outcomes (preeclampsia, gestational diabetes, obstructed labor, and infectious disease); fetal adverse outcomes (growth, gestational age, and developmental programming); and infant adverse outcomes. The evidence for all of these outcomes is contradictory (except for maternal infectious dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
170
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(177 citation statements)
references
References 147 publications
(258 reference statements)
4
170
1
2
Order By: Relevance
“…Recent narrative reviews suggested that the prevalence of vitamin D deficiency during pregnancy can be alarmingly high (e.g. 84% (Brannon and Picciano, 2011) (also see review (Ponsonby et al, 2010)). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent narrative reviews suggested that the prevalence of vitamin D deficiency during pregnancy can be alarmingly high (e.g. 84% (Brannon and Picciano, 2011) (also see review (Ponsonby et al, 2010)). …”
Section: Introductionmentioning
confidence: 99%
“…There is also preliminary evidence to suggest that vitamin D deficiency may be linked to a range of later adverse health outcomes in the offspring (Boucher, 1998, McGrath, 2001, Brannon and Picciano, 2011, Christesen et al, 2012, Thorne-Lyman and Fawzi, 2012, Zipitis and Akobeng, 2008, Ponsonby et al, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Cord concentrations are lower than maternal concentrations, therefore, if the mother is deficient so too will be the foetus [9]. Despite the lack of change/decline in 25OHD levels, levels of the biologically active vitamin D metabolite, 1,25 dihydroxy vitamin D [1,25(OH) 2 D], are known to increase by 100% or more during pregnancy [7,10]. This rise begins at 10-12 weeks gestation and reaches a maximum in the third trimester [10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the lack of change/decline in 25OHD levels, levels of the biologically active vitamin D metabolite, 1,25 dihydroxy vitamin D [1,25(OH) 2 D], are known to increase by 100% or more during pregnancy [7,10]. This rise begins at 10-12 weeks gestation and reaches a maximum in the third trimester [10]. Increased synthesis of the active vitamin D form is due to the enhanced production of 1a-hydroxylase in the decidua and placenta, as well as an oestrogen-dependent increase in vitamin D binding protein [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have linked maternal vitamin D status, as measured by circulating 25(OH)D, with placental function and fetal growth, pregnancy outcomes and offspring risk of chronic disease. [2][3][4] The mechanism by which vitamin D crosses the placenta is not yet clear. Recent literature reviews reported that the main mechanism is passive diffusion, as occurs with sex steroid hormones.…”
Section: Introductionmentioning
confidence: 99%